Improving accuracy of breeding values by incorporating genomic information in spatial-competition mixed models [Conjunto de datos] - Cappa, Eduardo Pablo; El-Kassaby, Yousry A.; Muñoz, Facundo; Garcia, Martin Nahuel; Villalba, Pamela Victoria; Klapste, Jaroslav; Marcucci Poltri, Susana Noemi (2020)
Supplementary information of a Eucalyptus grandis population, genomic and pedigree data including identity information of trees, family, and provenance of the paper entitled: Improving accuracy of breeding values by incorporating genomic information in spatial-competition mixed models. Mol Breeding 37, 125 (2017).